Complementation of a Dictyostelium discoideum thymidylate synthase mutation with the mouse gene provides a new selectable marker for transformation. - Chang, A C (1989)
A cDNA encoding mouse thymidylate synthase has been inserted 3' to the Dictyostelium discoideum actin 15 promoter in an E. coli-D.discoideum shuttle vector. When this construct was introduced into a D.discoideum thymidylate synthase mutant strain HPS400, stable transformants were obtained at high frequency. These transformants grew in standard axenic medium without requiring exogenous thymidine. This construct provides a second selectable marker for use in transformation of D.discoideum.